Sports Tourism and Social Media Storytelling: A multimodal perspective - Blanco-Gómez, María Luisa; Gómez-Ortiz, María José (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2024)
In the emotional narrative of sports event tourism, visual communication is key to persuading media consumers. Our aim is to examine the interplay between context (sports tourism) and text (visual and written) to shed light on the storytelling of blogs and online articles regarding sports tourism. Results show that the narrative sequence of the images, supported by text, highlights central values of sports, such as leadership, teamwork, and respect, in which the host city integrates. The emotions reflected in the corpus images point to the construction of a well-defined national identity in tourism social media when applied to sports events.